2021
DOI: 10.2169/internalmedicine.5850-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Resolution of a Case of TAFRO Syndrome Accompanied by Mediastinal Panniculitis, Adrenal Lesion, and Liver Damage with Hyperbilirubinemia

Abstract: TAFRO syndrome is a systemic inflammatory, lymphoproliferative disorder, but the pathophysiology of the disease is unknown. It is typically characterized by thrombocytopenia, anasarca, a fever, reticulin fibrosis, renal dysfunction, and organomegaly. However, other manifestations have been also reported. We encountered a 43-year-old man with TAFRO syndrome who showed mediastinal panniculitis, liver damage, and adrenal lesions in addition to the core signs. He achieved complete remission with combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…These presentations and the results of the lymph node biopsy led to the diagnosis of TA-FRO syndrome. The bilateral adrenal infarctions were not accompanied by adrenal insufficiency and spontaneously improved before the initiation of the treatments for TAFRO (2) 24 Female Adrenal infarction Bilateral 2 (2) 50 Male Adrenal infarction Unilateral 3 (2) 71 Male Adrenomegaly Unilateral 4 (2) 33 Male Adrenal infarction Bilateral 5 (2) 55 Male Adrenal infarction Bilateral 6 (2) 53 Male Adrenal infarction Bilateral 7 (2) 35 Male Adrenomegaly Bilateral 8 (4) 46 Male Adrenal infarction Unilateral 9 (6) 48 Male Adrenal hemorrhage Unilateral 10 (7) 43 Male Adrenomegaly Unilateral 11 (8) 19 Male Adrenal hemorrhage Bilateral 12 (8) 31 Female Adrenal hemorrhage Bilateral 13 (9) 48 Male Adrenal hemorrhage Bilateral 14(Our case) 53 Female Adrenal infarction Bilateral syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These presentations and the results of the lymph node biopsy led to the diagnosis of TA-FRO syndrome. The bilateral adrenal infarctions were not accompanied by adrenal insufficiency and spontaneously improved before the initiation of the treatments for TAFRO (2) 24 Female Adrenal infarction Bilateral 2 (2) 50 Male Adrenal infarction Unilateral 3 (2) 71 Male Adrenomegaly Unilateral 4 (2) 33 Male Adrenal infarction Bilateral 5 (2) 55 Male Adrenal infarction Bilateral 6 (2) 53 Male Adrenal infarction Bilateral 7 (2) 35 Male Adrenomegaly Bilateral 8 (4) 46 Male Adrenal infarction Unilateral 9 (6) 48 Male Adrenal hemorrhage Unilateral 10 (7) 43 Male Adrenomegaly Unilateral 11 (8) 19 Male Adrenal hemorrhage Bilateral 12 (8) 31 Female Adrenal hemorrhage Bilateral 13 (9) 48 Male Adrenal hemorrhage Bilateral 14(Our case) 53 Female Adrenal infarction Bilateral syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported in patients with TAFRO syndrome. In our literature search, we found 14 cases of TAFRO syndrome with adrenal abnormalities (2,4,(6)(7)(8)(9). We have summarized these cases in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these cases, we identified eight cases of TAFRO syndrome with adrenal abnormalities in the English literature (6)(7)(8)(9)(10)(11)(12). A summary of the 16 total cases, including the current case, is listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 10 cases exhibited bilateral adrenal abnormalities, and no apparent laterality was observed. In particular, eight out of nine cases for which detailed clinical data were available presented with abdominal pain as the first manifestation of TAFRO syndrome (7)(8)(9)(10)(11)(12). Nishimura et al reported that the incidence of abdominal pain as the first chief complaint was 50% (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation